A Chinese firm goes global : the Gree story - Chen, Zonglin; Zhou, Xibing (Paths International cases in modern Chinese business., 2015)
This book examines the success of Gree Electric Appliances (a major Chinese appliance manufacturer), taking a close look at Gree's marketing, branding, management strategies, and services, together with information on how they compete with overseas companies, and how they deal with intermediaries. The book also highlights the problems experienced at Gree, the challenges successfully conquered, and its possible future paths. As part of the practical new Cases in Modern Chinese Business series, the book offers revealing insights and analysis on how business is done in China. The series provides.